The consumer loan industry in Singapore - Ng, Irene (2015)
Consumer lending means doing business with individuals, from various age groups and income stratum, satisfying their financial needs through the provision of financial products and services. The developments of the consumer loan industry have been influenced by changes in the market structure, competitive behaviour and technological advancements. Above all, banks have realised that the changes in the economic, social and demographic environments have created new financial demands that need to be met. The consumer loan industry in Singapore has grown rapidly and undergone many changes in recent years. Competition is highly visible. It is thus appropriate to undertake a review of the consumer loan industry to examine the developing future trends in this market. The study can be basically divided into 3 main categories. The frrst section looks into the development of the consumer loan industry from the 1970s to the 1990s. The second section examines the forces of change that give rise to the present plethora of the consumer loan industry and takes a look at current consumer thinking in loans. Lastly, the study attempts to highlight the future trends in the consumer loan industry.